Investigation of Multilayered Film Structure Properties for Creation of Hydrogen Selective Membrane - Ryabchikov A. I. Aleksandr Ilyich; Golovkov V. M. Vladimir Mikhailovich; Sivin D. O. Denis Olegovich; Sokhoreva V. V. Valentina Viktorovna (Materials Science and Technologies, 2015)
Title screen